A Case Study of Students’ Difficulties in Learning Conditional Sentence at the Eleventh Grade Students’ of SMA N 4 Purworejo in the Academic Year of 2016/2017 - Satmoko Puji Laksana (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2019)
Conditional sentence becomes one of materials in grammar that is complex and difficult to be used by the students especially in senior high school. Identifying the difficulties of conditional sentence is essential to know how well the students master the materials. The objectives of this research are to describe the most difficult types of conditional sentence used by the students and to identify why the students get difficulties in learningconditional sentence. This research uses descriptive qualitative research. The subject of this research is the eleventh grade students (Class XI Bahasa) of SMA N 4 Purworejo. From the findings that the researcher has done, conditional sentence type 3 became the most difficult one. Based on the test, for each type of conditional sentence, type 3 is the highest with the total number of wrong answer are 116 (47.5%), then type 2 with thetotal number of wrong answer are 84 (34.4%), while type 1 is the lowest with the total number of wrong answer are 44 (18.1%). Added by the result of questionnaire as supporting instruments, the most difficult type of conditional sentence is conditional sentence type 3. The result shows that three students strongly agree and twenty students agree that conditional sentence type 3 is difficult. Then, one student strongly agrees and fourteen students agree that conditional sentence type 2 is difficult. While, just nine students agree that conditional type 1 is difficult. Morever, from the result of the interview and questionnaire, the researcher identifies the students’ difficulties in learning conditional sentence, they are the highest graduation is students are lack of vocabulary (66.67%), the second is having to eagerness to master the material (62.34%), the third is having negative attitude toward teaching and learning process (56.79%), the fourth is environment impact to learn English (55.55%), the fifth is not paying attention to the material (50.93%), the sixth is having negative attitude towards English and grammar (54.32%), and the last is the condition of the facilities is not good (22.22%).